Determination of cerebrospinal fluid adenosine deaminase activity cut-off for the diagnosis of tuberculous meningitis in Hong Kong. Issue 12 (18th May 2020) - Chan, Toby Chun Hei; Chen, Sammy Pak Lam; Mak, Chloe Miu; Ching, Chor Kwan; Luk, Kristine Shik; Tsang, Yat Ming; Leung, Daniel Cheuk Wa
Abstract : Aims: Tuberculous meningitis (TBM) is a severe infection which may lead to serious complication and mortality. Prompt diagnosis and treatment are essential. There is a need for a simple and fast laboratory test to differentiate TBM from other causes. Methods: Retrospective review was conducted for cerebrospinal fluid adenosine deaminase (CSF-ADA) activity which was measured at the Chemical Pathology Laboratory of Princess Margaret Hospital, the sole centre providing such service in Hong Kong, for 51 patients with suspected meningitis from nine local hospitals between June 2014 and July 2017. TBM diagnosis was defined by positive culture and/or nucleic acid amplification test result of Mycobacterium tuberculosis complex in CSF. Results: CSF-ADA activity was significantly higher in the TBM group (8.6±2.1 IU/L, n=8) than that of the non-TBM group (2.8±5.9 IU/L, n=43). The optimal clinical cut-off of 5.1 U/L for TBM diagnosis in our laboratory yielded 100% sensitivity, 91% specificity, positive likelihood ratio of 10.8 and negative likelihood ratio of 0. In rare circumstance, false elevation may be seen in non-tuberculous cause, such as central nervous system lymphoma and fungal infection. Conclusions: We recommend the use of CSF-ADA activity, which is a simple, fast and robust test for early differentiation of TBM from other causes, to facilitate timely initiation of antituberculous treatment and potentially improve patients' outcome.